Floriana Znanieckiego kategoria porządku – nieporządku w odczytaniu Lecha Witkowskiego a dyskurs pedagogii instytucjonalnych - Marynowicz-Hetka, Ewa (Chowanna, 2023)
In her article, Ewa Marynowicz-Hetka responds to Lech Witkowski’s postulate, formulated in his monograph on Florian Znaniecki. Witkowski suggests searching for “between” connections in analysis, thus expressing the trans-topicality of Znaniecki’s work. Marynowicz-Hetka is interested in searching for temporal and spatial bridges, for ways of connecting space and historical time with our present moment. Her analysis in this article focuses on transversally outlined concepts and approaches to practical activity, as clearly expressed in the reception of Florian Znaniecki’s work. Their frameworks and analogies can be found in recent conceptions of order and disorder, important for the socio-pedagogical horizon of thinking. This insight, formulated in Lech Witkowski’s book, constitutes the central premise of this article, its considerations inspired by the insights that the category of chaos present in Znaniecki’s work requires an intense focus on the content and manner of speaking about the following triad: order – disorder/chaos – re-ordering/new order. This insight also justifies a revisiting of the issue of the scope of transformations and institutional movements essential to the understanding of practical activity.